(untitled) (Bangladesh Journal of Medical Science, 2023)
Introduction: Sudden cardiac arrest is one of the most common causes of death in the world. Today, cardiopulmonary resuscitation in the prehospital phase, although crucial in the emergency care system, remains a weak link in the survival chain. Training in basic life support should begin in the school years in order to reach a larger population over time. The aim of the study was to assess the degree of readiness of students and their parents for the early implementation of training in basic life support. Materials and Methods: we surveyed 236 people, of which 118 students (group 1) of the primary school in Sumy and 118 - their parents (group 2). The survey was conducted anonymously. The questionnaire included 24 statements that determined the personal attitude to the need for early implementation of basic life support skills in primary school students, which later allowed us to determine the degree of readiness of students and their parents to solve this urgent problem for the world community. Correlation analysis was performed for groups 1 and 2 for more significant indicators. Results: the results of the study indicate that the level of readiness of students and parents contributes to the possibility of early implementation of resuscitation training in schools, which can help increase the number of people in communities who have basic life skills and will be ready to use them if needed. Conclusions: Thus, our research indicates that students and their parents are positive about learning basic life support in primary school and tend to think that mastering BLS skills will significantly increase students’ self-confidence when they witness an emergency. Bangladesh Journal of Medical Science Vol. 22 No. 01 January’23 Page : 145-153